Perancangan Sistem Reimburse Listrik Karyawan (Studi Kasus: PT Asuransi Sinar Mas) - Pancrastius Dimas Gunawan Aji Pamungkas (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Abstract The electricity replacement application is one of the applications needed by PT Asuransi Sinar Mas in order to replace electricity bills that have been issued by employees. The problem faced by employees is the excessive use of electricity so that employees need this electricity replacement system. Therefore, the author designed a system for replacing electricity costs at PT Asuransi Sinar Mas. This system uses the SQL programming language with the PEGA platform. Pega's platform that focuses on the Business Process Manager (BPM) makes it easy for writers to translate the needs needed by users into the system created, these needs are designed using the unified modeling language (UML) design method. With this application, employees can easily process electricity reimbursements.